A Study on Psychological Well-Being of Women Working in Southern Railways Tiruchirappalli - Dr.K.Maheswari**, K.S.Velmurugan*, (International Journal of Scientific Research and Management (IJSRM), 2017)
Mental health is the foundation for well-being and effective functioning for an individual and for a community and that of women is important both for their own health and for the well-being of their children and families. Different factors have significant influence on the psychological well-being, like poor nutrition, diseases, injuries and severe pain in body part etc, which can contribute to well-being issues and psychological distress. Working women statistics, women suffer high levels of physical, sexual and psychological abuse (Mankani, 2012). ‘Low birth weight, miscarriage and prematurity are the widespread problems in undernourished population that can be exacerbated by heavy and stressful work’. This study is aimed to assess the psychological well-being of women working in Southern Railways Tiruchirappalli. Objective of the study includes socio demographic profile of the respondents and assessment of the psychological well-being of women working in Southern Railways, Tiruchirappalli. The researcher has used descriptive research design, the universe of the present study comprises of 343 women working in Southern Railways, Tircuhirappalli.  Simple random sampling method was adopted to enquire 96 respondents for the study, which forms 1/3rd of the 343 universe. The researcher has used self prepared interview schedule pertaining to socio-demographic characteristics and a standardized tool on the psychological well-being scale developed by Ryff (1989). The major findings of the study revealed that majority of the respondents (63.5%) have moderate level of psychological well-being